PERILAKU ASUPAN NUTRISI BALITA BERHUBUNGAN DENGAN PERUBAHAN STATUS GIZI DARI BALITA KURANG GIZI YANG MENDAPAT PROGRAM PMT-P, PUSKESMAS KAWANGU SUMBA TIMUR - MARIA KARERI HARA (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2014)
Ekstra feeding for malnourished children in East In2012, in Eastern Sumba 21% of children under 5 were malnourished, at Kawangu Community Health Centre (KCHC) it was reported that 3.4% of children were underweight. This study investigated relationships between feeding behavior of child carers and nutritional status changes of children from KCHC. Research was crosssectional using 80 samples matching the inclusion criteria. Variables were feeding behaviors, and change in nutritional status. Data anthropometric measurements were taken to assess changes in nutritional status of children. Analysis used univariate and bivariate chi-square tests. Results indicated respondents were aged 26-35 (56,0%), had elementary school education (75,0%), although there was an increase in improvement in nutritional status (63.8%). There was an association between feeding behavior (p = 0.032) with changes in nutritional status. Feeding practices impacted positively upon improvements in child nutritional status. Future recommendations include upscaled health education as well as encouragement of use of local food sources.